Effect of teacher autonomy support on student engagement in physical education classrooms in a blended learning environment: the mediating role of performance expectancy and academic self-efficacy - Lianqiang Li; Detao Zeng (BMC Psychology)
Abstract Background With the rapid rise of online learning in higher education, blened learning models have become increasingly common. In this context, teacher autonomy-support strategies are widely used to help students engage more effectively and improve learning outcomes in environments that combine online and offline learning. While this approach offers new educational value and experiences, there has been limited focus on how autonomy-supportive teaching strategies enhance student engagement in physical education classes within blened learning environments. Methods This study developed a sequential mediation model to examine how perceived performance expectancy (PE) and academic self-efficacy (ASE) mediate students’ responses to teacher autonomy support (TAS), fostering cognitive, behavioral, emotional, and social engagement in a blended learning environment. The model was tested on non-physical education students at a full-time university in Chongqing, China. Findings The findings indicate that teacher autonomy support positively affects students’ behavioral, emotional, and social engagement in sports classes. Academic self-efficacy enhances cognitive, behavioral, emotional, and social engagement, while performance expectancy have a positive effect only on behavioral and social engagement. Performance expectancy and academic self-efficacy sequentially mediate the relationship between teacher autonomy support and student participation in physical education classrooms. Conclusions Teacher autonomy support, performance expectancy, and academic self-efficacy are significant predictors of student engagement in physical education classes, as performance expectancy and academic self-efficacy partially mediate the effect of teacher autonomy support on student participation. This study highlights the value of teacher autonomy support in blended online learning to boost student engagement in physical education, positively influencing innovation in higher physical education.